Using Technology to Promote Active and Social Learning Experiences in Health Professions Education - Ruckert, Elizabeth; McDonald, Paige; Birkmeier, Marissa; Walker, Bryan; Cotton, Linda; Lyons, Laurie; Straker, Howard; Plack, Margaret (Online Learning, 2014)
Time and space constraints, large class sizes, competition for clinical internships, and geographic separation between classroom and clinical rotations for student interaction with peers and faculty pose challenges for health professions educational programs. This article presents a model for effectively incorporating technology to overcome these challenges and enhance student engagement and interaction in traditionally face-to-face (FTF) health professions (physical therapy and physician assistant) curricula across learning environments (classroom to clinic). Four faculty members interested in redesigning a course or course unit(s) met with the IMPACT (Instructional Media and Programming to Advance Collaboration and Teaching) Initiative instructional design team. Instructional designers provided education, training, and support to faculty for increased use of technology within their course. Four exemplars using Blackboard, videos, VoiceThread®, and Twitter® are described. Themes and “lessons learned” were developed from each of the exemplars. A model emerged for integrating technology into health professions curricula with an emphasis on engaging students in active, realistic, and social learning environments. This model demonstrates how technology can be integrated successfully into traditionally FTF health professions curricula to support learning outcomes essential for practice.